Food taboos and nutritional assessment in people with ostomy in the amazon context (Research, Society and Development, 2022)
The increase in chronic diseases in recent years has rise the need for placement of ostomy bags. Changes occur in their lives, and food is impacted, through the food taboo people stop consuming certain foods, out of fear and as an attempt to prevent embarrassing situations. This study sought to verify the food taboos of people with ostomy, make a nutritional assessment and establish if there are correlations. This is a cross-sectional, descriptive and quantitative research, seventy seven individuals with intestinal and urinary ostomy were interviewed at the specialized referral unit, the data collected through the sociodemographic questionnaire verifying the type and character of ostomy and etiology, anthropometric evaluation (body mass index, arm circumference, arm muscle circumference and tritrital skinfold) in addition to the question "do you have a taboo/food belief?” In the case of an affirmative answer, which ones were asked. The results showed that 66% of the participants had food taboo, both men and women presented for shrimp and pork, even without a significant percentage of intolerances and allergies, these foods are part of culinary dishes in the region thus affecting socialization, but there was no significant correlation with nutritional status when evaluating body mass index (p=0.13), adequacy of Tritriital Skinfold (p=0.26) and arm circumference (p=0.59), and arm muscle circumference (p=0.74), demonstrating how much individual belief and society influence people's dietary choices, this can cause damage.